Caregiver "objective attitude" toward patients with neurodegenerative disease: Consequences for caregiver strain and relationship closeness. (2nd September 2021) - Zahir, Ali; Staffaroni, Adam M.; Wickham, Robert E.; Quinn, Carson M.; Sapozhnikova, Anna; Seidman, Jeffrey; Chiong, Winston
Abstract: Many caregivers of patients with neurodegenerative disease experience physical and psychological strain, which is associated with negative health outcomes. Caregiver strain may be partly attributable to negative emotional responses (e.g.of resentment) to the behavioral, cognitive, and physical changes associated with patients' disease. The philosopher Peter Strawson observed that in dealing with people who have neurological impairments, we often choose to suspend such emotional responses, adopting what he labeled the "objective attitude, " though this may come at the expense of our relationships with them. In this study, we assessed the mediating effect of caregivers' adoption of the objective attitude on caregiver strain and relationship closeness in the setting of disease progression. Caregivers of patients with neurodegenerative disorders ( n  = 215) completed the Clinical Dementia Rating, Relationship-Closeness scale, Caregiver Strain Index, and a novel questionnaire assessing the adoption of the objective attitude. A structural equation model assessing associations among these variables demonstrated good fit (χ 2 (88)=164.621, p  < 0.001; CFI = 0.929, RMSEA = 0.064.) and showed that adoption of the objective attitude mediated the association between disease progression and relationship closeness (total β= −0.233, 95% CI: −0.351, −0.113; indirect β= −0.483, 95% CI: −0.602, −0.364; direct β = 0.250, 95% CI: 0.117, 0.384), but did not mediate the association between disease progression and caregiver strain (total β = 0.323, 95% CI: 0.234, 0.412; indirect β = 0.089, 95% CI: −0.027, 0.206; direct β = 0.153, 95% CI: −0.043, 0.349). For future work, we propose longitudinal measurements of these constructs to test the directionality of associations and consideration of how models for caregiver support can draw upon interdisciplinary insights.